2016
DOI: 10.1080/15592324.2015.1136763
|View full text |Cite
|
Sign up to set email alerts
|

Stress promotes Arabidopsis - Piriformospora indica interaction

Abstract: The endophytic fungus Piriformospora indica colonizes Arabidopsis thaliana roots and promotes plant performance, growth and resistance/tolerance against abiotic and biotic stress. Here we demonstrate that the benefits for the plant increase when the two partners are co-cultivated under stress (limited access to nutrient, exposure to heavy metals and salt, light and osmotic stress, pathogen infection). Moreover, physical contact between P. indica and Arabidopsis roots is necessary for optimal growth promotion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Of the 4 genes associated with salinity stress tolerance traits identified in this study, P. indica-insensitive protein 2 is reportedly involved in salinity tolerance through its interaction with phytohormones (auxins, cytokinin, gibberellins, abscisic acid, ethylene, salicylic acid, jasmonates, and brassinosteroids) in Arabidopsis (Xu L. et al, 2018). When barley and rice roots were colonized by endophytic basidiomycete fungi (P. indica), the host plants enhanced performance under salinity stress (Baltruschat et al, 2008;Vahabi et al, 2016;Jogawat et al, 2016). The protein kinase superfamily is another important gene family that has been characterized in several plants; e.g., for drought tolerance in barley (Cieśla et al, 2016;Yang et al, 2017) and salinity stress tolerance in wheatgrass (Shen et al, 2001).…”
Section: Candidate Genes Reveal the Possible Molecular Basis Of Salinmentioning
confidence: 85%
“…Of the 4 genes associated with salinity stress tolerance traits identified in this study, P. indica-insensitive protein 2 is reportedly involved in salinity tolerance through its interaction with phytohormones (auxins, cytokinin, gibberellins, abscisic acid, ethylene, salicylic acid, jasmonates, and brassinosteroids) in Arabidopsis (Xu L. et al, 2018). When barley and rice roots were colonized by endophytic basidiomycete fungi (P. indica), the host plants enhanced performance under salinity stress (Baltruschat et al, 2008;Vahabi et al, 2016;Jogawat et al, 2016). The protein kinase superfamily is another important gene family that has been characterized in several plants; e.g., for drought tolerance in barley (Cieśla et al, 2016;Yang et al, 2017) and salinity stress tolerance in wheatgrass (Shen et al, 2001).…”
Section: Candidate Genes Reveal the Possible Molecular Basis Of Salinmentioning
confidence: 85%
“…In the context of the saprophytic traits of the microbes they concluded that the symbiotic interaction of these microbes requires non-compromised plant innate immune responses. Vahabi et al (2016) investigated beneficial and non-beneficial traits in the symbiotic interaction between P. indica and Arabidopsis roots and found that mild stress (limited access to nutrients, exposure to heavy metals or salt, light and osmotic stress, pathogen infections) promotes the benefits for the plant in the symbiosis. A physical contact was necessary, suggesting that the endophyte helps the plant after recognition of P. indica as a friend.…”
Section: Sa and Ja Two Phytohormones Involved In Quite Different Defmentioning
confidence: 99%
“…Under abiotic stress P. indica was also found to stabilize chlorophyll in rice leaves (Abadi and Sepehri 2016 ). By consequence, it increases the maximum quantum yield of PSII (Fv/Fm) (Vahabi et al 2016 ; Shahabivand et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%